Caries inhibition around gallium alloy by fluoride releasing resin cement - Nur'alim, Nasman (Universitas Padjadjaran, 2009)
Fluoride-releasing materials inhibit secondary caries. Gallium alloy has been developed to replace mercury-based amalgam. The purpose of this study was to test a new F releasing resin-ionomer cement for inhibition of 24 extracted human premolars. The experimental cavity (ARG) were filled using etching, priming, and F releasing resin-ionomer cement (All-bond 2 & Presinomer, Bisco) followed by condensation of gallium alloy (G Tokuriki Honten, Japan). Three different controls were used: gallium alloy only (G), no etching, Presinomer, gallium alloy (RG), etching, priming, non-F cement (All-bond C&B, Bisco) and gallium alloy (ACG) The teeth were thermocycled 500x, stored in humidor 28 days, then exposed to artificial caries for 21 days using a strep. mutans culture. Next, they were sectioned and examined by microradiography. The microradiographs were examined for the presence of a caries inhibition zone near the restoration and classified as strongly inhibited (SI), moderately inhibited (MI) or not inhibited (N) at the enamel and dentin wall. A Chi-square analysis showed that G is different from ARG, ACG is different from ARG, and RG is different from ACG (p<0.05). The results show that the fluoride-releasing resin-ionomer cement provided caries inhibition with or without etching and bonding and that etching and bonding alone is not as effective as fluoride release.